REACTION OF ULAMA ON FATWA CONTEMPORARY YUSUF AL-QARADHAWIY ABOUT SUICIDE BOMBING - Dahyul Daipon (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2020)
Fatwa Yusuf Al-Qaradhawiy about "Suicide Bombing" was born to respond to the bombing of istisyhaad "looking for shaheed" several times. In this case, Yusuf Al-Qaradhawiy said that using bombs as a tool and weapon that can kill enemy forces even your self is in the context of facing the enemy of Allah who is strong and sophisticated in his weapons where he relies on several arguments that include both the text of the doctrine (pen. Nash) or according to reason. The methodology used by Yusuf Al-Qaradhawi in his fatwa is to use the iqtihad intiqa’i method. This fatwa is for Qardhawiy indeed in the context of defending religion by taking into account at least three conditions namely First, knowing that the war that he followed was a war that was prescribed in religion (masyru'iyah). Second, jihad is carried out by the order of the leader (imam). Third, consider every action to be saved (not killed). Therefore there is no word of surrender or submission to be killed easily by unbelievers.